Improvement of flux pinning ability by tungsten oxide nanoparticles added in YBa2Cu3Oy superconductor. Issue 6 (15th April 2019) - Slimani, Y.; Almessiere, M.A.; Hannachi, E.; Mumtaz, M.; Manikandan, A.; Baykal, A.; Ben Azzouz, F.
Abstract: In this study, series of superconductor-tungsten oxide (WO3 ) nanoparticles composites, YBa2 Cu3 O7-δ /(WO3 )x, were produced via the solid-state reaction process. The structural, morphological, chemical compositions, electrical and magnetic properties were investigated using X-ray diffraction (XRD), scanning electron microscope (SEM) along with EDX system and physical properties measurement system (PPMS), respectively. The XRD, SEM and EDX analyses showed the successful formation of the Y-123 orthorhombic phase. The electrical resistivity measurements proved the occurrence of superconductivity in different samples. The magnetic results showed an improvement of critical current density (Jc ) and pinning ability in WO3 nanoparticles added Y-123 products. The dominant pinning mechanisms and the strength of pinning centers in various sintered products were examined and discussed. The measurements of zero-field-cooled (ZFC) and field-cooled (FC) magnetization versus temperature (M-T) indicated an increase in the magnitude of diamagnetic signal with the addition of WO3 nanoparticles in the Y-123 superconductor.